2016
DOI: 10.1073/pnas.1612024114
|View full text |Cite
|
Sign up to set email alerts
|

miR-17∼92 family clusters control iNKT cell ontogenesis via modulation of TGF-β signaling

Abstract: Invariant natural killer T cells (iNKT) cells are T lymphocytes displaying innate effector functions, acquired through a distinct thymic developmental program regulated by microRNAs (miRNAs). Deleting miRNAs by Dicer ablation (Dicer KO) in thymocytes selectively impairs iNKT cell survival and functional differentiation. To unravel this miRNA-dependent program, we systemically identified transcripts that were differentially expressed between WT and Dicer KO iNKT cells at different differentiation stages and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…Some miRNAs also play important roles in regulating immune function and maintaining immune homeostasis, such as miR-223-3p and miR-155-5p (120122). It is not surprising that abnormal expressions of miRNAs involving immune function can potentially contribute to the development of autoimmune diseases (123, 124). Recent studies have revealed that some miRNAs are also involved in the development of AITD, and most of them have been found to be intensively involved in modulating the differentiation or activation of immune cells and immune response (Table 1).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%
“…Some miRNAs also play important roles in regulating immune function and maintaining immune homeostasis, such as miR-223-3p and miR-155-5p (120122). It is not surprising that abnormal expressions of miRNAs involving immune function can potentially contribute to the development of autoimmune diseases (123, 124). Recent studies have revealed that some miRNAs are also involved in the development of AITD, and most of them have been found to be intensively involved in modulating the differentiation or activation of immune cells and immune response (Table 1).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%
“…Mir‐150 is required for iNKT cell maturation and its loss results in increased interferon‐ γ (IFN‐ γ ) production, miR‐181 is essential for the early development of iNKT cells and Let‐7 miRNAs specifically target Promyelocytic leukemia zinc finger protein (PLZF) expression during iNKT cell development in the thymus . Recently, it was shown that the miRNA cluster miR17~92 regulates iNKT cell development through regulation of transforming growth factor‐ β …”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are short noncoding RNAs with a length of 18-22 nucleotides that cause mRNA cleavage and subsequent degradation by binding to the complementary 3′-UTR of the mRNA. miR-17 has been shown to control iNKT cell oncogenes is via modulation of TGF-β signaling [24], and TGF-β signaling plays an important role in Treg differentiation [25]. Therefore, we evaluated the effect of miR-17 on TGFBR II expressed by T cells and found that the expression of TGFBR II on the cultured CD4 + T cells was significantly decreased after transfecting with miR-17, and siTGFBR II resulted in a similar reduction in the frequency of Tregs, suggesting that miR-17 regulated the Treg differentiation by inhibiting TGFBR II expression.…”
Section: Discussionmentioning
confidence: 99%